2011
DOI: 10.1088/0957-4484/22/32/325601
|View full text |Cite
|
Sign up to set email alerts
|

An environment-friendly preparation of reduced graphene oxide nanosheets via amino acid

Abstract: Chemically modified graphene has been studied in many applications due to its excellent electrical, mechanical, and thermal properties. Among the chemically modified graphenes, reduced graphene oxide is the most important for its structure and properties, which are similar to pristine graphene. Here, we introduce an environment-friendly approach for preparation of reduced graphene oxide nanosheets through the reduction of graphene oxide that employs L-cysteine as the reductant under mild reaction conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
167
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(190 citation statements)
references
References 38 publications
23
167
0
Order By: Relevance
“…9 and enhanced green fluorescent protein. 66 Our present data are in good agreement with previous reports, indicating that resveratrol reduction effectively increased the size of rGO particles.…”
Section: Notessupporting
confidence: 93%
See 1 more Smart Citation
“…9 and enhanced green fluorescent protein. 66 Our present data are in good agreement with previous reports, indicating that resveratrol reduction effectively increased the size of rGO particles.…”
Section: Notessupporting
confidence: 93%
“…Recently, Mhamane et al 64 have reported a facile singlestep synthesis of highly water-dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of GO. Our data indicate that GO reduction can be performed using resveratrol, which is in agreement with earlier studies using various natural products such as vitamin C, 65 l-cysteine, 66 and humanin 8 as reducing agents. The results also show that the properties of resveratrol-converted graphene nanosheets are comparable to those of chemically reduced graphene nanosheets.…”
Section: Xrd Analysis Of Go and Res-rgosupporting
confidence: 92%
“…It shows that the GO might be reduced, the aromatic structure restored, and the reduction improved. Similar features and trends have been observed for the reduction of GO with L-ascorbic acid 37 and L-cysteine, 38 baker's yeast, 18 and E. coli. 21 Fernández-Merino et al 37 suggested that the maximum red-shift value can be used as a standard to estimate the performance of the reducing agent.…”
Section: Resultssupporting
confidence: 77%
“…[40][41][42][43] Gt powder (2 g) was mixed with 80 mL H 2 SO 4 and 20 mL HNO 3 in an ice bath. KMnO 4 (12 g) was slowly added to the mixture.…”
Section: Go Synthesismentioning
confidence: 99%